Paesaggi fiabeschi e meravigliosi viaggi nelle commedie di Carlo Goldoni e Carlo Gozzi: Caratteristiche comuni fra le diverse visioni di teatro dei due grandi autori - Török, Tamara (Verbum – Analecta Neolatina, 2019)
Both Carlo Goldoni and Carlo Gozzi, leading Venetian playwrights of the 18th century, are regarded as reformers of the Commedia dell’Arte, but while Goldoni followed the direction of realism, Gozzi insisted on using certain elements of the above mentioned genre, completing it with exotic environments and magical episodes, all realized on stage with the help of the Baroque stage machinery. The rivalry between the two authors is one of the most interesting episodes of the history of 18th century theatre, and its most exciting period is undoubedly the one when Goldoni, after the successes of his character comedies and before writing his most developed choral comedies, hesitated for a few years, searching for new ways of expression, and wrote tragicomedies in Gozzi’s style, entering thus in an open competition with his rival. These tragicomedies were written at the end of the 1750s, in verse, with completely unrealistic plots, and with charactres who live in exotic countries, far away from Venice. Also in Paris, in the last phase of his career, Goldoni started to write again some fairy tale-like comedies, among the characters of which we find the typical figures of the Commedia dell’Arte. The intention of the present study is to confront the dramaturgical roles and the characteristics of the magic travels in Goldoni’s and Gozzi’s comedies in different moments of their careers, especially in Il genio buono e il genio cattivo (The Good Spirit and the Evil Spirit) by Goldoni and La donna serpente (The Serpent Woman) by Gozzi, with a hint also to how they use the exotic environments in La sposa persiana (The Persian Bride) (Goldoni) and Turandot (Gozzi).